Fibrin biopolymer incorporated with antimicrobial agents: a proposal for coating denture bases - Venante, Helena Sandrini; Chappuis-Chocano, Ana Paula; Marcillo-Toala, Oscar Oswaldo; Da Silva, Rafaela Alves; Da Costa, Rodrigo Moreira Bringel; Pordeus, Mariana Domingues; Barraviera, Benedito [UNESP]; Junior, Rui Seabra Ferreira [UNESP]; Lara, Vanessa Soares; Neppelenbroek, Karin Hermana; Honório, Heitor Marques; Porto, Vinicius Carvalho (MDPI, 2021)
The characteristics of the denture base surface, in combination with the oral environment, promote the colonization and development of Candida albicans biofilm, which is the main cause of denture stomatitis. This study evaluated the effectiveness of fibrin biopolymer with digluconate chlorhexidine or Punica granatum alcoholic extract to prevent C. albicans biofilm. Conventional heat polymerized and pre-polymerized poly(methyl methacrylate) (PMMA) circular specimens (102 mm) were fabricated (n = 504) and randomly divided into groups: no treatment (control-CT), fibrin biopolymer coating (FB), fibrin biopolymer with P. granatum (FBPg), or digluconate of chlorhexidine (FBCh) coating. The specimens were inoculated with C. albicans SC5314 (1*107 cells/mL) and incubated for 24, 48, and 72 h. Crystal violet and colony-forming unit assays were used to quantify the total biofilm biomass and biofilm-living cells. A qualitative analysis was performed using confocal laser scanning microscopy. Data obtained are expressed as means and standard deviations and were statistically analyzed using a three-way analysis of variance (p = 0.05). The FBPg and FBCh groups inhibited the growth of C. albicans biofilm in both PMMA materials analyzed, with FBCh performing better in all periods evaluated (p < 0.0001). The colony forming unit (CFU) assay showed that the FB group favored the C. albicans biofilm growth at 24 h and 48 h (p < 0.0001), with no differences with CT group at 72 h (p = 0.790). All groups showed an enhancement in biofilm development up to 72 h (p < 0.0001), except the FBCh group (p = 0.100). No statistical differences were found between the PMMA base materials (p > 0.050), except in the FB group (p < 0.0001). Fibrin biopolymer, albeit a scaffold for the growth of C. albicans, when combined with chlorhexidine digluconate or P. granatum, demonstrated excellent performance as a drug delivery system, preventing and controlling the formation of denture biofilm.
Keywords: Acrylic resin; CAD-CAM; Candida albicans; Complete denture; Denture stomatitis